Covalent organic framework without cocatalyst loading for efficient photocatalytic sacrificial hydrogen production from water - Xuejiao Du; Haifeng Ji; Yang Xu; Shiwen Du; Zhaochi Feng; Beibei Dong; Ruihu Wang; Fuxiang Zhang (Nature Communications)
Abstract Metals are typically essential as either integral components within photocatalysts or as cocatalyst modifiers to enable efficient artificial photosynthesis, such as water splitting and carbon dioxide reduction. However, developing photocatalysts that function effectively without metal cocatalysts remains challenging due to their cost and scarcity. Here we show a nonstoichiometric β-ketoenamine-linked covalent organic framework that operates without cocatalysts, achieving hydrogen production rates of 15.48 mmol·g⁻¹·h⁻¹ from seawater and 22.45 mmol·g⁻¹·h⁻¹ from water with an ascorbic acid scavenger under visible light. It outperforms many reported platinum-modified covalent organic frameworks and metal-containing inorganic photocatalysts. The enhanced performance is attributed to its broad light absorption edge extending to approximately 660 nm, efficient charge separation, and the presence of abundant active oxygen sites derived from carbonyl groups, which exhibit a low hydrogen-binding Gibbs free energy change. This work lays the groundwork for designing cost-effective photocatalytic systems suitable for large-scale hydrogen production.